The magic school bus at the waterworks - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1986)
When Ms. Frizzle, the strangest teacher in school, takes her class on a field trip to the waterworks, everyone ends up experiencing the water purification system from the inside.
Keywords: Waterworks -- Juvenile literature; Hydrology -- Juvenile literature